Modelling and image reconstruction evaluation of a scintillation camera with silicone photomultiplier - Md Ali, Sham FIrdaus; Saripan, M. Iqbal; Muhammad Noor, Ahmad Shukri; Rokhani, Fakhrul Zaman; Hashim, Suhairul; Dong, Xianling (Shiraz University of Medical Sciences, 2022)
Background: Recent research on photon detection has led to the introduction of a silicone photomultiplier (SiPM) that operates at a low voltage and is insensitive to magnetic fields. Objective: This work aims to model a scintillation camera with a SiPM sensor and to evaluate the camera reconstructed images from gamma ray projection data. Material and Methods: The type of study in this research is experimental work and analytical. The scintillation camera, modelled from an SiPM sensor array SL4-30035, coupled with a scintillation material Caesium Iodide doped with Thallium (CsI(Tl)), is used in the experimental part. The performance of the camera was evaluated from reconstructed images by a back-projection technique of a radioactive source Caesium-137 (Cs-137). Results: The experiments conducted with a 1 µCi Cs-137 radioactive source have revealed that the bias voltage (Vbias) of the SiPM needs to be set to 27.8 V at an operating temperature between 43 °C to 44 °C. The radioactive source has to be placed within a 1 cm distance from the sensor to obtain the optimum projection data. Finally, the back-projection technique for image reconstruction with linear interpolation pre-processing has revealed that the Ram-Lak filter produces a better image contrast ratio compared to others. Conclusion: This research has successfully modelled a scintillation camera with SiPM that was able to reconstruct images with an 86.4% contrast ratio from gamma ray projection data.